2022
DOI: 10.3390/en15186852
|View full text |Cite
|
Sign up to set email alerts
|

McCARD Criticality Benchmark Analyses with Various Evaluated Nuclear Data Libraries

Abstract: International Criticality Safety Benchmark Evaluation Project (ICSBEP) criticality analyses were conducted using the McCARD Monte Carlo code for 85 selected benchmark problems with 7 evaluated nuclear data libraries (ENDLs): ENDF/B-VII.1, ENDF/B-VIII.0, JENDL-4.0, JENDL-5.0, JEFF-3.3, TENDL-2021, and CENDL-3.2. Regarding the analyses, it was confirmed that the keff results are sensitive to the ENDL. It is noted that the new-version ENDLs show better performance in the fast benchmark cases, while on the other h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…This model has improved the Geant4 accuracy of calculated cross-sections versus measured data from the EXFOR database (Shin 2015) and is recommended by the Geant4 collaboration for photons and neutrons with energies below 20 MeV (The Geant4 Collaboration 2024). Of note, it has been shown that the interpretation and implementation of EDL in MC engines might impact sampled cross-sections and energy spectra, as discussed elsewhere (Park et al 2022).…”
Section: Introductionmentioning
confidence: 92%
“…This model has improved the Geant4 accuracy of calculated cross-sections versus measured data from the EXFOR database (Shin 2015) and is recommended by the Geant4 collaboration for photons and neutrons with energies below 20 MeV (The Geant4 Collaboration 2024). Of note, it has been shown that the interpretation and implementation of EDL in MC engines might impact sampled cross-sections and energy spectra, as discussed elsewhere (Park et al 2022).…”
Section: Introductionmentioning
confidence: 92%